Clinical Characteristics of Inflammatory Bowel Disease Patients Requiring Long‐Term Parenteral Support in the Present Era of Highly Effective Biologic Therapy. Issue 5 (10th September 2020) - Kurin, Michael; Anderson, Alyce; Ramos Rivers, Claudia; Koutroumpakis, Filippos; Centa, Patricia; Bender‐Heine, Juliette; Kozak, Gina; Kramer, Elisabeth; O'Keefe, Stephen J.; Whitcomb, David C.; Levinthal, David J.; Koutroubakis, Ioannis E.; et al.
Abstract: Background: Despite advances in the medical management of inflammatory bowel disease (IBD), a subset of patients may require extensive surgery, leading to short‐bowel syndrome/intestinal failure requiring long‐term home parenteral nutrition (PN) or customized intravenous fluid (IVF) support. Our aim was to further define the characteristics of IBD patients requiring home PN/IVF. Methods: This is an observational study from a prospective IBD research registry. Patients receiving long‐term home PN/IVF support during 2009–2015 were identified and compared with remaining IBD patients. Demographics, surgical history, smoking, narcotic use, IBD treatment, healthcare charges, and presence of biomarkers were reviewed. The IBD‐PN group was stratified into 3 groups based on median healthcare charges. Results: Of 2359 IBD patients, there were 25 (1%, 24 with Crohn's disease) who required home PN/IVF, and 250 randomly selected IBD patients matched for disease type formed the control population. Median duration of PN use was 27 months (interquartile range, 11–66). PN use was significantly associated with smoking, narcotic use, IBD‐related operations, and lower quality‐of‐life scores. Among IBD‐PN patients, 7 of 25 (28%, 3 after use of teduglutide) were able to successfully discontinue this modality. Median healthcare charges in the IBD‐PN group were $51, 456 annually. Median charges in the controls were $3427. Period prevalence mortality was 11.5% in IBD‐PN and 3.8% in controls. Conclusions: IBD patients requiring long‐term home PN/IVF support are a small minority in the present era of immunomodulator/biologic therapy. These refractory patients have a 15‐fold increase in annual median healthcare charges compared with control IBD patients.